Müsilaj sorunu ve karakterizasyonu - KAYHAN, FİGEN ESİN (My University, 2022)
Bütün dünyada olduğu gibi ülkemizde de nüfus artışının getirdiği kentleşme ve sanayileşme; çeşitli çevre sorunlarına yol açmaktadır. Son yıllarda, denizlerde planktonik ve bentik alg çoğalmalarından kaynaklanan müsilajlı organik madde oluşumu artmıştır. Denize kıyısı olsun veya olmasın tüm şehirlerin sıvı atık yükü en sonunda denizlere ulaşmaktadır. Bu kirlilik yükü zamanla birikmekte ve doğal şekilde temizlenemeyecek kadar büyümektedir. Bu derlemede hem dünya denizlerinde hem de ülkemiz denizlerinde müsilaj olayının oluşumu, gelişimi ve sonuçları irdelenmeye çalışılmıştır.

As in the whole world, urbanization and industrialization brought about by population growth in our country; causes various environmental problems. In recent years, the formation of mucilage organic matter resulting from planktonic and benthic algae eruptions of the seas has increased. The liquid waste load of all cities, whether they have a coast or not, reaches the seas in the tenth. This pollution load accumulates over time and grows too large to be cleaned by natural means. In this review, the formation, development and results of the mucilage phenomenon in both the world’s seas and our country’s seas have been tried to be examined.
Mucilage problem and its characterization
Keywords: Müsilaj; Marmara Denizi; deniz kirliliği; Mucilage; Sea of Marmara; marine pollution